Activity of Plant Extracts from Clove, Thyme, and Turmeric Against Streptococcus spp Bacteria Causing Oral and Gum Diseases (Sebha University Conference Proceedings, 2024)
In recent decades, the problem of bacterial resistance to antibiotics has increased, prompting researchers to seek effective natural alternatives. This study aims to evaluate the effects of plant extracts from clove (Syzygium aromaticum), thyme (Thymus vulgaris), and turmeric (Curcuma longa) on Streptococcus bacteria causing oral and gum diseases. A total of 60 bacterial swabs were collected from patients with dental caries and gingivitis and cultured on blood agar. After identifying the bacterial species using the API 20 Strep system, plant extracts were prepared using ethanol and water.The results showed that alcoholic extracts were generally more effective than aqueous extracts. The clove alcohol extract exhibited the highest efficacy against Streptococcus salivarius with an average inhibition zone of 21 mm, followed by thyme alcohol extract with an average of 17 mm, and turmeric alcohol extract with an average of 16 mm. These findings indicate that using alcohol as a solvent increases the effectiveness of plant extracts, as alcohol can extract biologically active compounds at higher concentrations. Aqueous extracts were less effective, with thyme water extract showing the lowest efficacy with an average inhibition zone of 12 mm.